South of the crisis : a Latin American perspective on the late capitalist world - Corradi, Juan E., 1943- (London : Anthem Press, 2010)
The book offers an unorthodox account of why and how global capitalism has entered a phase of unsustainable crises of accumulation and legitimacy, and examines the different exit strategies open to Latin American countries.
Impending storms : fiscal intemperance and moral dilemmas -- The troubles at the center -- The response -- A paucity of thought and action -- The new world in a changed world -- Other capitalisms : what Latin Americans can learn from those who do it well -- Rethinking Latin American dependency -- Latin America in the world of late capitalism -- A garden of forking paths -- The challenge of inclusion.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Social integration -- Latin America; Global Financial Crisis, 2008-2009.; Capitalism; Latin America -- Economic policy; Latin America -- Social policy